MODEL KEPEMIMPINAN VISIONER KEPALA SEKOLAH DALAM PELAKSANAAN KEGIATAN EKSTRAKURIKULER - Herni Herni (Kelola: Journal of Islamic Education Management, 2020)
This research aims to determine the competitive extracurricular activities, to understand the visionary leadership of the school principal who comes in leading the implementation of the extracurricular activities and to find out the visionary leadership model of school principals in developing the extracurricular learning in SMAN 1 Palopo. This research was a qualitative study. It used managerial, psychological, sociological perspective, religious approaches. The instrument used namely observation data collection, interview, and documentation. The data analysis of the research was using data reduction, presentation of data, triangulation, as well as the withdrawal of conclusion. The results of the study conclude that: 1) The extracurricular activities in a SMAN 1 Palopo consists of the scouts, extracurricular activities basketball, and marching extracurricular activities 2) The visionary leadership of the school principal who comes in leading the implementation of the extracurricular activities in sen SMAN 1 Palopo can be seen from the perspective of a clear vision and mission planning, having high innovation, high exemplary and discipline, and the school principal becomes the agent of change. 3) Visionary leadership model of school principals in developing the competitive extracurricular learning in senior high school 1 Palopo consisting of The formulation of vision, the transformation of vision, the implementation of the vision, as well as completing the facilities and infrastructure.